REDUCING THE HEAT STRESS ON MAIZE DURING SPRING SEASON BY USING SOME BIO STIMULANTS - Athraa.A .Al- Omairi; I. H. H. Al-Hilfy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate the effect of bio stimulators )chitosan and Appetizer( in reducing the heat stress on maize during spring season. Field experiment was conducted at the experimental farm, Coll. of Agricultural Engineering Sciences, University of Baghdad, Al-Jadiriya, Iraq, during the seasons of 2020 and 2021. The experiment was laid out in Randomized Complete Blocks Design within split plot arrangement, with three replicates. Where the main plots included two cultivars of maize )Baghdad3 and cultivar 5018(, while the sub plots included five levels of chitosan and Appetizer:(soaking seeds with Chitosan at a concentration of 100 and 500 mg L-1, and spraying with Chitosan 100 mg L-1, and spraying Appetizer in two and three stages in addition to the two control treatments, which are soaking seeds with distilled water and dry seeds. The results showed that the cultivar 5018 was superiored in grain yield 11.82 and 11.08 Mg ha-1 in both seasons. The treatment of spraying Chitosan gave the highest grain yield 13.26 and 12.94 Mg ha-1, spraying the Appetizer in two stages gave 13.32 and 12.54 Mg ha-1 , and spraying Appetizer in three stages gave 13.70 and 12.97 Mg ha-1 for both seasons. The interaction was significant in most of the studied traits. So we recommend the use of Chitosan spray at a concentration of 100 mg L-1 and Appetizer spray at a concentration of 1.25 ml L-1 in two or three stages to reduce the effect of heat stress on maize planted in the spring season to increase grain yield.